IMAGE DAYA TARIK WISATA ALAS KEDATON DI DESA KUKUH, MARGA, TABANAN - I Made Darma Oka; Ida Ayu Ketut Sumawidari (Soshum: Jurnal Sosial dan Humaniora, 2013)
Tabanan regency is one of tourist destination area in Bali that has many tourism areas spreading over the district and the village. One of tourism destination has been famous in Tabanan regency is Alas Kedaton tourist destination.The location of Alas Kedaton tourist destination is about 7 km from the Tabanan city. The objective of this research is (a) to know the image Alas Kedaton tourist destination by the tourist, (b) to define the marketing sustainability strategic which will be applied in the future. The data were used are secondary data and deep interview with the informan who understood about the Alas Kedaton tourist destination. Based on the research that Alas Kedaton tourist destination has positive image. The strategy that can applied is focusing on: product brand identity, spirit of the caracteristic brand, the marketing focus to the domestic market and joint venture with travel agent to market Alas Kedaton tourist destination in the future.